Evaluation of Powerhouse Cavern for the SachKhas Hydroelectric Project in Himachal, India - Rathore, Ajender; Panthi, Krishna Kanta (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
Evaluation of an underground powerhouse cavern’s stability is a challenging task and needs to be carried out carefully by taking care of its location, orientation and dimensioning. This article deals with the stability evaluation of a large underground powerhouse cavern, which is located at the toe of the valley side slope where the depth varies between 59m (minimum) and 70m (maximum). The planned powerhouse cavern has a dimension consisting 130m length, 23m wide and 48 m high. The manuscript evaluates the extent of pre-construction phase engineering geological investigations of the project, discusses on the selection of input parameters and carries out assessment on the displacement conditions at the cavern and also assesses the extent of yielded zone at the toe slope. Finally, recommendations are suggested on the location and orientation of the powerhouse cavern, uncertainties involved in numerical analysis and boundary conditions for 2D and 3D models under gravitational field stress.HYDRO Nepal JournalJournal of Water Energy and EnvironmentIssue: 20Page: 23-30